Cost-effectiveness analysis of SARS-CoV-2 infection prevention strategies including pre-endoscopic virus testing and use of high risk personal protective equipment - Ebigbo, Alanna (Endoscopy, 2021)
Background  Infection prevention strategies to protect healthcare workers in endoscopy units during the post-peak phase of the COVID-19 pandemic are currently under intense discussion. In this paper, the cost-effectiveness of routine pre-endoscopy testing and high risk personal protective equipment (PPE) is addressed. Method  A model based on theoretical assumptions of 10 000 asymptomatic patients presenting to a high volume center was created. Incremental cost-effectiveness ratios (ICERs) and absolute costs per endoscopy were calculated using a Monte Carlo simulation. Results  ICER values for universal testing decreased with increasing prevalence rates. For higher prevalence rates (≥ 1 %), ICER values were lowest for routine pre-endoscopy testing coupled with use of high risk PPE, while cost per endoscopy was lowest for routine use of high risk PPE without universal testing. Conclusion  In general, routine pre-endoscopy testing combined with high risk PPE becomes more cost-effective with rising prevalence rates of COVID-19.